Recurrent Nasal-Type Extranodal Natural Killer/T-Cell Lymphoma with Meningeal Involvement - Sylvester Homsy; Ralph Kamel; Mark Raden; Yevgeniy Skaradinskiy (Case Reports in Hematology, 2021)
Extranodal natural killer/T-cell lymphoma nasal type (NNKTL) is a type of non-Hodgkin’s lymphoma that has been associated with Epstein–Barr virus (EBV). It has an aggressive behavior, known for predilection to metastasize to different organs. Central nervous system (CNS) spread from a primary location has been reported. Different modalities of treatment such as chemotherapy and radiation therapy have been employed in the management of this disease. Severe toxicities of currently available treatment have made clinicians seek more targeted therapies using molecular profiling. We present a 44-year-old Hispanic patient who was diagnosed with an early-stage NNKTL and treated with the modified SMILE regimen for 6 cycles. His EBV DNA PCR turned undetectable and remained so throughout the treatment. He sustained complete right vision loss due to right optic nerve invasion by the tumor, leading to prophylactic intravitreal methotrexate to the contralateral eye. The patient achieved good response with minimal residual disease. He was supposed to start radiation as a sequential therapy. However, the acute development of severe headache and confusion lead to a complete workup showing leptomeningeal spread. He eventually succumbed to the disease.